On gambling research, social science and the consequences of commercial gambling. Issue 1 (2nd January 2018) - Livingstone, Charles; Adams, Peter; Cassidy, Rebecca; Markham, Francis; Reith, Gerda; Rintoul, Angela; Dow Schüll, Natasha; Woolley, Richard; Young, Martin
Abstract: Social, political, economic, geographic and cultural processes related to the significant growth of the gambling industries have, in recent years, been the subject of a growing body of research. This body of research has highlighted relationships between social class and gambling expenditure, as well as the design, marketing and location of gambling products and businesses. It has also demonstrated the regressive nature of much gambling revenue, illuminating the influence that large gambling businesses have had on government policy and on researchers, including research priorities, agendas and outcomes. Recently, critics have contended that although such scholarship has produced important insights about the operations and effects of gambling businesses, it is ideologically motivated and lacks scientific rigour. This response explains some basic theoretical and disciplinary concepts that such critique misunderstands, and argues for the value of social, political, economic, geographic and cultural perspectives to the broader, interdisciplinary field of gambling research.